STRATEGI PENGEMBANGAN INDUSTRI MIKRO KECIL MENENGAH (STUDI KASUS INDUSTRI PEMOTONGAN AYAM PEDAGING) DI KECAMATAN TAMPAN KOTA PEKANBARU - Wibowo. S Bonggal Prima Aldo; Harahap Azwar; Setiawan Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was purpose to determine the strengths, weaknesses, opportunities and threats of developing the chicken slaughtering business in Tampan District, Pekanbaru City are. And to know the Strategy for the Development of Broiler Slaughtering Business in Tampan District, Pekanbaru City. This research uses primary data and secondary data. Data collection techniques in this study were observation, interviews and questionnaires. The method used in this research is quantitative descriptive analysis with the SWOT analysis technique. The results of this research show that the results of the evaluation of internal factors using the IFAS matrix, obtained a total score of 3,130 in the strength factor and 3,446 in the weakness factor, which means that the score obtained is above the average 2.5 This shows that the broiler slaughtering business in Tampan District, Pekanbaru City is able to optimize its strengths, namely good relations with labor, conducting market research, good product quality, affordable prices and meeting production capacity so that it can cover existing weaknesses. within the business unit. The results of the evaluation of the EFAS matrix above show that the total score on the opportunity factor is 3,335 and the threat factor is 3,491, which means that the score obtained is above the average of 2.5. This shows that the broiler slaughtering business in Tampan District, Pekanbaru City takes advantage of existing opportunities such as supportive economic conditions, market demand, healthy lifestyles, population development and technological developments for production so as to overcome threats within the business unit. From the results of the Cartesian diagram in research with the title of the development strategy of small and medium micro industry (Case Study of Chicken Slaughtering Industry) in Tampan District, Pekanbaru City, the position is in the B quadrant which means Quadrant B shows the factors that are considered important, management has been successfully implemented as desired / hope and very satisfying so that it must be maintained.Keywords: Micro, Small and Medium Industry, Chicken Slaughtering